Prognostic significance of cathepsin V (CTSV/CTSL2) in breast ductal carcinoma in situ. Issue 2 (23rd August 2019) - Toss, Michael; Miligy, Islam; Gorringe, Kylie; Mittal, Karuna; Aneja, Ritu; Ellis, Ian; Green, Andrew; Rakha, Emad
Abstract : Aims: Cathepsin V (CTSV/CTSL2) is a lysosomal cysteine proteinase and plays a role in extracellular matrix degradation. It is associated with poor prognosis in invasive breast cancer (IBC), but its role in breast ductal carcinoma in situ (DCIS) remains unclear. In this study, we aimed to evaluate the prognostic significance of CTSV in DCIS. Methods: CTSV protein expression was immunohistochemically assessed in a well-characterised and annotated cohort of DCIS comprising pure DCIS (n=776) and DCIS coexisting with IBC (n=239). CTSV expression was analysed in tumour cells and surrounding stroma, including its association with clinicopathological parameters and outcome. Results: In pure DCIS, high CTSV expression was observed in 29% of epithelial tumour cells and 20% of surrounding stroma. High expression in both components was associated with features of poor prognosis including higher nuclear grade, hormone receptor negativity and HER2 positivity. In addition, stromal CTSV expression was associated with larger DCIS size, comedo-type necrosis and high proliferation index. DCIS associated with IBC showed higher CTSV expression than pure DCIS either within the epithelial tumour cells or surrounding stroma (p<0.0001 and p=0.001, respectively). In DCIS/IBC, CTSV expression was higher in the invasive component than DCIS component either in tumour cells or surrounding stroma (both p<0.0001). CTSV stromal expression was associated with invasive recurrence independent of other prognostic factors in patients treated with breast conserving surgery (HR=3.0, p=0.005). Conclusion: High expression of CTSV is associated with poor outcome in DCIS and is a potential marker to predict DCIS progression to invasive disease.